An ultrasound-assisted nitrogen protection system for sustainable indigo dyeing of cotton fabrics. Issue 13 (July 2023) - Wang, Kangkang; Meng, Yuchen; Luo, Qingliang; Wang, Liming; Wang, Rongwu; Qin, Xiaohong
The traditional process of denim dyeing is highly environmentally damaging due to high temperature used for reduction and dyeing as well as the heavy use of sodium dithionite. It can be efficient if dyeing can be carried out with an environmental reducing agent under nitrogen protection or if the liquor ratio can be reduced. However, at such a low liquor ratio, dye molecules form agglomerates, which results in inefficient dye-uptake and uneven dyeing. This study investigated the possibility of applying ultrasound in conjunction with nitrogen protection to the dyeing of cotton fabrics with indigo reduced by the reducing agent DK. Comparing the reducing agent DK with the other reducing agents, it was found that reducing agent DK had stronger reducing and better properties for indigo dyed fabrics. Furthermore, the synergistic effect of nitrogen protection and ultrasound prevented the early oxidation and agglomeration of the leuco-indigo. It was evident that there was an increased contact area between the leuco-indigo and the cotton fiber, as well as a decrease in the crystallinity of the cellulose macromolecules. And the increased amorphous region of the cellulose macromolecules facilitated indigo-leuco's penetration into the fiber, resulting in enhanced dyeing depths and uniformity. In addition, orthogonal experiments and gray clustering analysis were utilized to optimize the dyeing process. As a result of the optimized dyeing process, the K / S and S values of dyed denim fabric reached 16.70 and 0.12, respectively, which was 42% and 72% higher than the traditional sodium dithionite dyeing process. It was found that the dyeing liquid was more susceptible to biological and chemical degradation. In addition, the total economic costs were reduced by 11.702%. It is conceivable that eco-friendly dyeing strategies presented here have superior dyeing properties which can significantly enhance the sustainability of denim dyeing processes.